Prospective study to find out the role of gastric aspirate examination by Ziehl-Neelsen staining (ZN staining) and cartridge based nucleic acid amplification test (CB-NAAT) as a diagnostic method in childhood tuberculosis - Arora, Akansha; Jain, Anil; Karnawat, B. S.; Kumawat, Rakesh (International Journal of Contemporary Pediatrics, 2018)
Background: Tuberculosis in children has been relatively neglected mainly because clinical diagnosis has low specificity, radiological interpretation is subject to inter-observer variability and the tuberculin skin test is a marker of exposure, not disease. The recent introduction of Cartridge based nucleic acid amplification test has significantly transformed the diagnostics of tuberculosis in adults but its application for Paediatric Tuberculosis is under evaluation. Therefore, authors conducted a study on role of gastric aspirate examination by ZN stain and Cartridge based nucleic acid amplification test in the diagnosis of childhood Tuberculosis. Methods: Authors did a prospective hospital-based study from Nov 2016 to Nov 2017 consisting of 100 randomly selected patients suspected of tuberculosis who had their gastric aspirate tested for CBNAAT and ZN stain for acid fast bacilli (AFB) along with Mantoux test and other routine investigations. Chi square test was used. Results: Culture positive tuberculosis was found in 21 out of 100 children. The sensitivity, specificity, positive predictive value and negative predictive value for CBNAAT were 76.1%, 98.7%, 94.1% and 93.9% and for ZN stain were 47.6%, 98.7%, 90.9% and 87.6% respectively. Positive history of contact (p value 0.0217), reactive Mantoux test (p value < 0.001) and low socioeconomic status were independently associated with a positive CBNAAT result. Conclusions: Analysis of gastric aspirate samples with CBNAAT is a sensitive and specific method for rapid diagnosis of pulmonary tuberculosis in children who cannot produce sputum. Compared with microscopy, CBNAAT offers better sensitivity and its scale up will improve access to tuberculosis diagnostics in children.